Stenotrophomonas maltophilia outer membrane vesicles elicit a potent inflammatory response in vitro and in vivo. Issue 8 (17th October 2016) - Kim, Yoo Jeong; Jeon, Hyejin; Na, Seok Hyeon; Kwon, Hyo Il; Selasi, Gati Noble; Nicholas, Asiimwe; Park, Tae In; Lee, Sang Hwa; Lee, Je Chul
Abstract : Stenotrophomonas maltophilia has become one of the most prevalent opportunistic pathogens in hospitalized patients. This microorganism secretes outer membrane vesicles (OMVs), but the pathogenesis of S. maltophilia as it relates to OMVs has not been characterized. This study investigated the cytotoxic activity of S. maltophilia OMVs and their ability to induce inflammatory responses both inÃÂ vitro and inÃÂ vivo . Stenotrophomonas maltophilia ATCC 13637 and two clinical isolates were found to secrete spherical OMVs during in vitro culture. OMVs from S. maltophilia ATCC 13637 were cytotoxic to human lung epithelial A549 cells. Stenotrophomonas maltophilia OMVs stimulated the expression of proinflammatory cytokine and chemokine genes, including interleukin (IL)-1ÃÂ², IL-6, IL-8, tumor necrosis factor-ÃÂ± and monocyte chemoattractant protein-1, in A549 cells. Early inflammatory responses such as congestion and neutrophilic infiltrations and profound expression of proinflammatory cytokine and chemokine genes were observed in the lungs of mice injected with S. maltophilia OMVs, and were similar to responses elicited by the bacteria. Our data demonstrate that S. maltophilia OMVs are important secretory nanocomplexes that elicit a potent inflammatory response that might contribute to S. maltophilia pathogenesis during infection. Abstract : Stenotrophomonas maltophilia OMVs are important secretory nanocomplexes that elicit a potent inflammatory response that may contribute to S. maltophilia pathogenesis during infection.